INFORMATION TECHNOLOGY UTILIZATION AND ITS IMPACT ON SERVICE EFFECTIVENESS IN WEST JAKARTA - Pujiastuti, Nur Raisha; Triwinata, Jennie; Maryani, Dedeh (Moestopo International Review on Social, Humanities, and Sciences, 2025)
The rapid advancement of information technology has significantly influenced the public service sector, including immigration services. This study examines the effect of information technology utilization on service effectiveness at the West Jakarta Immigration Office, with a particular focus on the role of employees in optimizing the "Smart Immigration Service" system. Using a quantitative approach, data were collected from 120 immigration officers through structured questionnaires. The analysis was conducted using multiple linear regression to assess the relationship between technology adoption and key indicators of service effectiveness, including accuracy, speed, transparency, and user satisfaction. The findings indicate that effective utilization of information technology positively and significantly impacts service performance, enabling faster processing times, reduced errors, and improved accessibility for the public. Moreover, employees’ digital competence plays a critical mediating role, ensuring that technological tools are applied optimally to meet service standards. This study highlights the strategic importance of continuous digital skills development for employees to sustain and enhance the quality of public services in the era of digital governance.